Linked Working: Generating Success on the World's Largest Professional Networking Website - Frank Agin; Lewis Howes (Journal of Applied Sports Management, 2012)
The following book excerpt comes from Chapter 2 of the eBook LinkedWorking. The book is available in digital bookstores and on www.linkedworking.com.